Sufism in Java: The Meeting Point Between Sufism and Javanese Mysticism - Nashichuddin, Ach. (UIN Maulana Malik Ibrahim Malang, 2006)
Wali Songo is a clerical preacher who is not only an Islamic prophet but also a carrier of Sufism in Java. This paper reviews sufism in Wali Songo era and the meeting point between sufism and Javanese mysticism. Seen from their teachings, they are adherents of the flow of Sunni Sufism that many adopt the teachings of Imam Al-Ghazali. In developing their teachings they established an educational institution called pesantren, an educational institution which at the same time provides a dormitory as a residence for the santri. In spreading Islam they are easily accepted by the Javanese community. This cannot be separated from the teachings they developed, the teachings of Sufism which have similarities with the mystical teachings held by the people of Java. The meeting point between Sufism and Javanese mysticism is the main factor in the success of Wali Songo’s mission in Java. It results in Javanese Islam, a combination between Islamic teaching and Javanese culture. Wali Songo adalah seorang pengkhotbah klerus yang bukan hanya seorang nabi Islam tapi juga pembawa tasawuf di Jawa. Makalah ini mengulas sufisme di era Wali Songo dan titik temu antara sufisme dan mistisisme Jawa. Dilihat dari ajaran mereka, mereka menganut aliran tasawuf Sunni yang banyak mengadopsi ajaran Imam Al-Ghazali. Dalam mengembangkan ajaran mereka, mereka mendirikan sebuah institusi pendidikan yang disebut pesantren, sebuah institusi pendidikan yang pada saat yang sama menyediakan asrama sebagai tempat tinggal para santri. Dalam menyebarkan Islam mereka mudah diterima oleh masyarakat Jawa. Hal ini tak lepas dari ajaran yang mereka kembangkan, ajaran tasawuf yang memiliki kesamaan dengan ajaran mistik yang dipegang oleh masyarakat Jawa. Titik temu antara tasawuf dan mistisisme Jawa merupakan faktor utama dalam keberhasilan misi Wali Songo di Jawa. Ini menghasilkan Islam Jawa, kombinasi antara ajaran Islam dan budaya Jawa.